CHANGES IN THE DENTAL PULP CALCIFICATIONS WITH A LAMELLAR CONCENTRIC STRUCTURE AND CALCIFICATIONS WITH AN AMORPHOUS TO FINELY GRANULAR STRUCTURE - Aleksova, Pavlina; Sali, Ferija; Aliu, Adem; Nikolovski, Bruno; Nikolovska, Vera Radojkova; Nastov, Nebojsa (Journal of Morphological Sciences; Vol 6 No 2 (2023): JMS, 2023)
The aim of the study was to inspect change in the pulp with dental calcifications by different structure. Material and method: we carried out the research on 40 pulps after indicated tooth extraction, during which we made a vertical section of the teeth and removed the pulps, and 60 extirpated pulps from teeth with an endodontic diagnosis of pulpitis chronica. With the method of light microscopy, and by using standard differential histo-chemical coloring, results were obtained on the Institute of Pathology of the Faculty of Medicine in Skopje. Results: 2 morphological images of changed pulp were obtained with the method of light microscopy with the application of standard differential histochemical staining: (1) dental pulp with calcifications with a lamellar concentric structure; (2) dental pulp with calcifications present with an amorphous to finely granular structure. In both groups, a reduction of cellularity in the connective tissue is observed, with evident but gradual hyalinization, which takes the form of wider areas or tracks, dissociated from relatively preserved loose connective tissue. Pulps containing nodular calcifications show a certain degree of congestion of blood vessels, in contrast to dispersed and irregularly shaped calcifications. Keywords: dental pulp, dental calcification, hystopathological analysis.